Contemporary Leadership Challenges (IntechOpen, 2023)
Social and behavioral science has for decades studied and recognized leadership as a social exchange between leaders and followers. But leadership is rather complex, and as such, it tends to lead to an increased interest within and across different disciplines. This book is an attempt to provide theoretical and empirical framework to better understand leadership challenges in various contexts. The authors cover an array of themes that span from an individual level to an organizational and societal level. In this volume, two sections are presented. The first section based on individual level focuses on different leadership styles and abilities, and the other section provides theories to understand leadership in public administration, in industrial settings and in nonprofit organizations.